miR-133: A Suppressor of Cardiac Remodeling? - Li, Ning; Zhou, Heng; Tang, Qizhu (Frontiers in Pharmacology, 2018)
Cardiac remodeling, characterized by mechanical remodeling and electrical remodeling, is a significant pathophysiological process involved in almost all forms of heart diseases. MicroRNAs (miRNAs) are a group of 20-25 nt non-coding RNAs, which regulate gene expression primarily through mRNA degradation or post-transcriptional repression in a sequence-specific manner. In the human genome, there are three known miR-133 genes: miR-133a-1, miR-133a-2 and miR-133b found on chromosomes 18, 20 and 6 respectively, which are mainly expressed in muscle tissue and appear to repress the expression of non-muscle genes. Increasing evidence indicates that miR-133 participates in the proliferation, differentiation, survival, hypertrophic growth and electrical conduction of cardiac cells, which are essential for cardiac fibrosis, cardiac hypertrophy and arrhythmia. Nevertheless, the roles of miR-133 in cardiac remodeling are ambiguous and the mechanisms are also sophisticated, involving many target genes and signaling pathways, such as Rhoa, MAPK,TGFβ/Smad, PI3K/Akt, etc. Therefore, in this review, we summarize the critical roles of miR-133 and potential mechanisms in cardiac remodeling.